Aleksander Birkenmajer jako wizytator Zbiornicy Księgozbiorów Zabezpieczonych we Wrocławiu - Nowicki, Ryszard (Biblioteka Uniwersytecka w Poznaniu, 2013)
Jeden z najwybitniejszych polskich bibliologów XX wieku prof. Aleksander Birkenmajer przeprowadził w 1949 roku na zlecenie Ministerstwa Oświaty pierwszą w swojej karierze bibliotekarskiej wizytację Biblioteki Uniwersyteckiej oraz Zbiornicy Księgozbiorów Zabezpieczonych we Wrocławiu. W instytucjach znajdowały się poddane ochronie materiały biblioteczne. Do Zbiornicy Księgozbiorów Zabezpieczonych w latach 1947-1949 zwieziono z terenu Dolnego Śląska około 900 000 tomów, głównie poniemieckiej proweniencji. Bibliolog w sporządzonym sprawozdaniu wskazał na występujące problemy oraz sposoby ich przezwyciężenia. Wysoko ocenił pracowników, którym przyszło działać w trudnym powojennym okresie. Birkenmajer okazał się wnikliwym, rzetelnym oraz obiektywnym wizytatorem. Sprawozdanie jest cennym dokumentem źródłowym pozwalającym poznać fragment historii wrocławskiej zbiornicy oraz Biblioteki Uniwersyteckiej. Powinno być wykorzystane w przyszłych pracach badawczych związanych z odbudową bibliotek i bibliotekarstwa na Dolnym Śląsku oraz w Polsce.

One of the most prominent Polish bibliologists of the twentieth century, Prof. Aleksander Birkenmajer, conducted in 1949 his first ever library inspection, commissioned by the Ministry of Education, at the University Library and the Secured Book Collection Repository in Wrocław. Both institutions held at the time library materials that were under special surveillance. Between 1947 and 1949, the Repository received about 900,000 volumes of mainly German provenience from Lower Silesia. In his subsequent report, Birkenmajer indicated the existing problems and proposed some ways to overcome them. He also highly praised the staff in charge of the collections who demonstrated their commitment and expertise in such harsh working conditions in this hard post-war period. Aleksander Birkenmajer proved to have been an insightful, solid, highly efficient and objective inspector. His Report is a valuable document and source material for a better understanding of the history of the Wrocław-based Repository and the University Library in Wrocław. Undoubtedly, the report should be included in any future research work concerning the reconstruction and rebuilding of libraries and librarianship in Lower Silesia and in Poland.
Aleksander Birkenmajer as the inspector of the Secured Book Collection Repository in Wrocław
Keywords: Aleksander Birkenmajer; preservation of library resources; Wrocław; Lower Silesia; book repository; 20th century; ochrona zbiorów bibliotecznych; Dolny Śląsk; zbiornica książek; XX wiek